Privileges in Printmaking - Marlise Rijks (Early Modern Low Countries)
The Low Countries became a centre of printmaking in the early modern period. Printmaking was a disruptive image-technology because it produced images as multiples on an unprecedented scale. With its success also came problems. One was that copying became a problem as it had not been before in the visual arts. This article discusses three approaches used by early modern printmakers to dealing with the problems presented by copying and the fact that prints came in multiples. The first was to acquire privileges as legal protection against copying. Privileges are usually seen as the predecessors of copyright, but here it is argued that this is only part of the story and that they also served as a claim of reliability. A second approach was to take full advantage of the opportunities presented by the fact that prints came in multiples, and to produce images as efficiently as possible, in effect endlessly copying the same images. A third approach was to purposefully ignore the technological possibilities of printmaking and instead produce small print runs or slightly different states of one image. These approaches, it is argued, were related both to technological possibilities and to changing ideas about the (visual) arts, showing how the meanings of concepts such as ‘invention’ and ‘skill’ were shifting at this time.